2010
DOI: 10.4314/njps.v23i1-2.54924
|View full text |Cite
|
Sign up to set email alerts
|

The effect of administration of amodiaquine on some Parameters of neurobehaviour of wistar rats

Abstract: Summary:The effect of administration of Amodiaquine (AQ) on some parameters of neurobehaviour of Wistar rats was carried out. Twenty adult Wistar rats weighing between 160-190g were divided equally into four groups. Group 1 served as the control, while groups 2, 3 and 4 were the experimental groups. The control group received distilled water. Groups 2 and 3 were treated with 8.75mg/kg and 17.50mg/kg respectively of AQ for three days, while group 4 was treated with 8.75mg/kg of AQ for six days. Neurobehaviour t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…These findings are in line with other studies even when repeated treatment has been given [3, 10, 35]. ASAQ was also found responsible of significantly higher events rate than other antimalarials in the literature [3, 29]. However, one recent study shows that AEs were no more numerous in ASAQ group than in AL one, even in cases of readministration [36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are in line with other studies even when repeated treatment has been given [3, 10, 35]. ASAQ was also found responsible of significantly higher events rate than other antimalarials in the literature [3, 29]. However, one recent study shows that AEs were no more numerous in ASAQ group than in AL one, even in cases of readministration [36].…”
Section: Discussionsupporting
confidence: 88%
“…Abnormal behavior was common although the literature reports behavioral changes as rare AEs of 4-aminoquinoline derivatives (including amodiaquine) and the summary of product characteristics (SmPC) does not mention it among psychiatric disorders [27, 28]. One study about effect of administration of amodiaquine on rats highlighted various behavioral disorders due to drug effects [29]. However, it is not excluded that these (subjective) effects were over-reported considering the fact of participating in a clinical trial was a new experience for both parents and child.…”
Section: Discussionmentioning
confidence: 99%
“…AQ is currently deemed a safe option for the treatment of malaria (Massaga et al, 2008;Otuechere et al, 2012;Saka et al, 2012b). Despite this classification, recent studies noted that AQ negatively affects multiple organs (Ajani et al, 2008;Ekong et al, 2008;Ajeigbe et al, 2012;Abolaji et al, 2014;Heidari et al, 2014). We found that AQ treatment disrupts spermatogenesis in a dose-dependent whereas 5 mg/kg (B), 10 mg/kg (C), and 15 mg/kg (D) AQ treatments induced a significant increase in the number of apoptotic germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of AQ, however, is also associated with organ damage, including hepatotoxicity (Larrey et al, ). Closer investigation of AQ‐mediated effects in rats have demonstrated a dose‐dependent effect on behavior, including total locomotor activity, central square frequency, and anxiety (Ekong et al, ); increased gastric acid secretion and altered the gastrointestinal mucosal integrity (Ajeigbe et al, ); elevated levels of reactive oxygen species, lipid peroxidation, protein carbonylation, and mitochondrial depolarization (Heidari et al, ); hypotensive and bradycardic effects due to altered K + channels and extracellular Ca 2+ influx (Adaramoye and Almeida, ); as well as side effects on indices of cardiovascular disease, such as serum total cholesterol, high‐versus‐low density lipoprotein and cholesterol concentration, and atherogenic index (Ajani et al, ; Adebayo et al, ). Co‐administration of artesunate and AQ was also shown to alter markers of liver function and lipid peroxidation in female rats (Abolaji et al, ).…”
Section: Introductionmentioning
confidence: 99%